2011
DOI: 10.1063/1.3574904
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanowires length on performance of crystalline silicon solar cell

Abstract: Silicon-nanowire (Si-NW) array, prepared by an electroless chemical-etching method, shows excellent optical antireflection property over a wide spectral bandwidth. The influence of the wire length on the optical antireflection property and the solar cell performance were studied for both the Si-NW array solar cells and the planar solar cells. The reflectance of NWs solar cells is almost invariable and much lower than that of the planar solar cells but the performance of planar solar cells is the best. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 13 publications
2
51
0
Order By: Relevance
“…The SiNWs arrays were then formed adopting a developed silver-induced wet-chemical-etching process in an aqueous buffered HF and AgNO 3 etching solution at 25 1C [23,34]. The etching time was 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SiNWs arrays were then formed adopting a developed silver-induced wet-chemical-etching process in an aqueous buffered HF and AgNO 3 etching solution at 25 1C [23,34]. The etching time was 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…While it is clear inserting SiNWs improves the PV device performance, further experimental work is necessary to understand the underlying mechanism (s) for SnS/SiNWs/Si devices. In addition, due to the large surface-to-volume ratio, the SiNWs have a high surface recombination rate [22,23]. SiNW surface passivation is an even more challenging task due to their small size and the fact that multiple facets with different crystalline orientations are exposed.…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al reported that careful control of doping profiles was necessary to avoid Auger recombination at the surface of nanostructured crystalline Si solar cells [14]. Li et al and Jung et al investigated Si nanowire (NW) array solar cells; longer NWs exhibited a lower optical reflectance over a wide spectral range, but did not improve the PV performance due to surface recombination [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…From the literature, it has been realized that the 2D graphene, 2D metal dichalcogenides and their nanocomposites have great potentials to replace the solar cells made from silicon that are currently being used. The majority of solar cells on the market are single-junction silicon wafer devices including single crystal and multicrystalline silicon, which are known as first generation solar cells [208][209][210] . Their main drawback is associated with their indirect optical band gap that requires a thick active layer for the solar conversion and thus costly fabrication of large area materials.…”
Section: Solar Cellsmentioning
confidence: 99%